Study on transfer characteristics of pressure fluctuation in a prototype pump-turbine. Issue 1 (January 2021) - Li, J W; Liu, X R
Abstract: Considering unit 3 in Zhanghewan pumped storage power station as the research object, transfer characteristics of pressure fluctuation at the vaneless area were studied from the dominant frequencies, the fractional amplitude and the fractional phase at four different measuring points. It was revealed that the variation trends of pressure fractional amplitude (50Hz and 100Hz) versus output agreed well at the four points, and the phase difference between the four points varied very small with increasing of output under different water heads. This research could provide instructive inspiration for solving the vibration problems in pumped storage power station, and provide useful thinking for optimizing hydraulic design of the pump-turbine.